Deconstruction Jacques Derrida: Deconstruction In The Novel Sang Keris By Panji Sukma - Rera Rizki Andika; Teguh Supriyanto; Nas Haryati Setyaningsih (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
The difference in understanding between writers and readers in interpreting the meaning or value of literature can be called deconstruction. This research aims to (1) describe the structure of the social conditions of society in the novel Sang Keris written by Panji Sukma, and (2) deconstruct other values that have been found, as a sign of logocentrism in the novel. This research is descriptive qualitative research using data cards as a tool. The data in this study are in the form of fragments of dialog sentences between characters and narratives. The data collection technique in this research uses heuristic reading technique and the data analysis technique used is hermeneutic technique. Based on the research, it can be concluded that the novel Sang Keris tends to tell stories of the past. There are a number of deconstructed meanings or social values in the novel that can be integrated into today's society. These values include: (1) loyalty, (2) courage, (3) honor, (4) self-discovery, (6) morality, (7) love and sacrifice, and others. This deconstructive thinking can be implemented for students to identify various layers of meaning in studying literary texts or used by other researchers for other studies.